Intercultural Communication Among the Bugis Community In Fostering Harmony Within The Buton Society - S. Jalaluddin; Hastuti; Muhammad Rizal Ardiansah Putra (Jurnal ISO: Jurnal Ilmu Sosial, Politik dan Humaniora, 2024)
This study aims to understand and explain how intercultural communication between the Bugis and Buton ethnic groups fosters harmony within the Pajalele community in Baubau City and to identify the barriers faced by the Bugis in establishing harmony with the Buton community. A qualitative approach with a Symbolic Interactionism method was used. The study involved 7 informants: 3 Ambonese, 3 Bugis, and 1 Community Leader. Data was collected through participatory observation, in-depth interviews, and document analysis, which were then analyzed thematically to identify effective communication in different cultural contexts. The results indicate that there is distinct yet complementary communication between the Bugis and Buton ethnic groups. The Bugis people have successfully fostered harmony within the Buton community according to the concepts of Thought, Self, and Social. The communication barriers identified include differences in language, cultural values, and the ongoing development of stereotypes and prejudices between the two ethnic groups